APPLICATION OF HYDROACOUSTIC METHODS IN GEOCHEMICAL RESEARCH OF POLLUTANTS DISTRIBUTION IN THE SURFACE LAYER OF BOTTOM SEDIMENTS - YEMELIANOV, Volodymyr; NASIEDKIN, Yevhen; FEDOSEIENKOV, Serhii; KOSHLIAKOVA, Tetiana (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article presents the results obtained during the long-term field studies of the characteristics of the sedimentary matter metal-containing component distribution within the territories of industrial cities, in particular, Zaporizhia city. Based on field contact and remote studies, one of the aspects of the problem was studied, namely the peculiarities of iron concentrations distribution in the surface layer of bottom sediments of the Dnipro river. Key practical approaches to the application of a new complex method of field observations are outlined, which combine the possibilities of express planar surveying with the determination of geochemical characteristics of river sediments. The methodology of combining contact geochemical studies of iron distribution in surface bottom sediments with the performance of a side view of a remote route survey using sonar is substantiated. Herewith, the possibility of determining the lithological differences of the surface layer of bottom sediments under the conditions of determining the average concentrations of iron for the main material types of sediments is assumed. The results of two-year research based on the data of fieldwork revealed promising perspectives for the development of such a complex of observations in the case of systematization of the direction, additional testing of the technological component in various test areas of the water area, as well as the development of an appropriate methodological foundation.
Keywords: environmental geology; bottom sediments; remote route survey; hydroacoustic methods; contact geochemical studies